2015
DOI: 10.1111/jog.12724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an in‐house real‐time polymerase chain reaction method to identify group B streptococcus colonization in pregnancy

Abstract: The in-house qPCR test has high sensitivity in detecting GBS colonization. The high negative predictive value helps to avoid unnecessary use of antibiotics in uncolonized women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The qPCR reaction showed a specificity of 73.6% when compared to the culture. This result is consistent with that reported by Yeung et al 38 (73.1%), who targeted the cpsG gene locus of the SGB capsular polysaccharide. Both PCR assays presented an NPV of 100%.…”
Section: Discussionsupporting
confidence: 93%
“…The qPCR reaction showed a specificity of 73.6% when compared to the culture. This result is consistent with that reported by Yeung et al 38 (73.1%), who targeted the cpsG gene locus of the SGB capsular polysaccharide. Both PCR assays presented an NPV of 100%.…”
Section: Discussionsupporting
confidence: 93%
“…The negative control should not have an amplification curve for the GBS target, while the positive control should be positive for the two targets tested. To ensure high sensitivity in the PCR, the cutoff point was set at a threshold cycle value of C t = 40 [10, 11].…”
Section: Methodsmentioning
confidence: 99%
“…PCR methods have reported to have higher sensitivity and detection rates than conventional screening culture, which is viewed as the gold standard method for GBS detection . Previous studies were reported sensitivities for culture were 42.3–68.4%, whereas sensitivity of PCR was 99.6% .…”
Section: Discussionmentioning
confidence: 99%